EFFECT OF MAGNETIC FIELD ON THE ROTATION CURVES OF SPIRAL GALAXIES - ( Nim: 10314028), WULANDARI
Discrepancies between expected and observed rotation curves in spiral galaxies are commonly interpreted as a proof for the existence of dark matter. The existence of dark matter can explain the flat rotation curves observed in the outer radii. However, some rotation curves of spiral galaxies exhibit a rising feature at large distance from the galactic center. The spiral galaxies’ components such as disk, gas, bulge, and dark matter halo are not sufficient to accomodate that feature. The addition of magnetic field contribution to the rotation curve of spiral galaxies is proposed in some literature to explain the rising feature. In this Final Project the author reviewed four data of rotation curve of three spiral galaxies, i.e. NGC 2841, NGC 6946, and NGC 7331 in SPARC catalogue obtained by Spitzer in 3.6 micrometer and M31 in Chemin et al. (2009), whose profiles of azimuthal magnetic field are available. The rotation curve of NGC 2841 and M 31 show rising features in SPARC data. For each galaxy the author investigated three cases: decomposition of the rotation curves into disk, gas, bulge, and dark matter halo components, decomposition into four components plus fixed additional contribution from magnetic field, and decomposition into four components plus free (adjusted) additional contribution from magnetic field. Decomposition scenarios using four components with magnetic field result in the better fitting resuts. Setting the contribution of magnetic field free in the rotation curve fitting gives better results in term of the smaller reduced chi square, in such case the rotation speed values ranging from 50 – 100 km/s. Whereas, fitting with second scenario provides values less than 10 km/s. However, according to SánchezSalcedo et al. (2014), large magnetic fields will give a too large vertical force that can break gas in the field of galaxies If this is true, then the fittings with the second decomposition scenario are considered to be more reasonable physically, moreover the difference of the reduced chi-square values between the two scenarios are not huge.